Axillary breast: Navigating uncharted terrain - Medha A Bhave (Indian Journal of Plastic Surgery)
Introduction: Axillary breast is a common condition that leads to discomfort and cosmetic problems. Liposuction alone and open excision are two techniques used for treatment. Materials and Methods: This study assesses the results of treatment in 24 consecutive patients, operated between 2005 and 2015.All patients had Kajava class IV masses. Three were treated by liposuction alone, while 21 were treated by open axillaplasty with limited liposuction. Results: One patient treated by liposuction alone had to be re-operated for a residual lump, while with axillaplasty, no major complications were observed and the results were uniformly good. Discussion: Certain points of technique emerged as major determinants in obtaining the best results. In brief, these are: a) limited skin excision; b) placing elliptical incisions within the most lax, apical axillary skin, irrespective of the location of the lump; c) raising skin flaps at the level of superficial fascia; d)meticulous dissection and preservation of the nerves, especially the second intercostobrachial; f) judicious liposuction for eliminating dog ears and axillary sculpting only; g) avoiding drains. Conclusion: Open axillaplasty with limited liposuction is the best way to minimise complications and produce good results.